Non-Surgical Management of Post-Cesarean Endomyometritis Associated With Myometrial Gas Formation - John R. Ebright; Julie Moldenhauer; Bernard Gonik (Hindawi Limited, 2000)
We present a case of post-cesarean delivery, nonclostridial endomyometritis in which uterine (myometrial) gas formation raised concern for myonecrosis and need for hysterectomy. The patient fully recovered without surgery. Myometrial gas formation in this setting and in an otherwise stable patient may be an insufficient reason for hysterectomy. Infect. Dis. Obstet. Gynecol. 8:181-183; 2000.